The psychosocial costs of post employment of overseas workers a research agenda - Samonte, Elena L. (1992)
This paper addresses the problem of psychosocial costs of employment of overseas workers by discussing the full cycle of employment (from pre-employment to postemployment) and the attendant psychosocial processes in each stage. It utilizes Homan's Equity Theory to discuss the risks involved. It underscores the costs involved in staying in the Philippines and how such costs tilt the balance in favor of the rewards from working abroad. Moreover, it proposes a research agenda that seeks to establish an empirically based concept of psychosocial costs and identify its predictors.
Keywords: Filipino foreign workers -- Employment; Filipino foreign workers -- Psychological aspects; Filipino foreign workers -- Social aspects